Contralateral protective effect against repeated bout of damaging exercise: A meta-analysis - Jeon, S.; Kang, M.; Ye, X. (Research in Sports Medicine, 2023)
The purpose was to summarize the studies examining the contralateral protective effect on the maximal strength in the subsequent bout of muscle-damaging exercise. The literature search was conducted through CINAHL plus, SportDiscus, and PubMed. Hedge`s g effect size (ES) and 95% confidence intervals (CIs) were computed using a random effects model. From 14 papers and 25 ESs, the mean ES for contralateral repeated bout effect (CL-RBE) on 1-, 2-, and 3-day post maximal strength were -0.61 (95% CI = -0.80, -0.41), -0.50 (95% CI = -0.67, -0.33), and -0.74 (95% CI = -1.01, -0.48), respectively. For moderator analyses, the mean ESs were not influenced by type (isometric vs. isokinetic) of strength, but CL-RBE on maximal strength was influenced by duration (=6 weeks) between bouts. Therefore, the meta-analysis demonstrated that an initial bout of exercise induces the protective effect on contralateral limb muscles regardless of the different type of strength, but can be affected by different duration (=6 weeks) between exercise bouts.